2020
DOI: 10.3390/nu12051368
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Provider-Level Socio-Demographic Determinants of Diet Quality of Preschool-Aged Children Attending Family Childcare Homes

Abstract: Since food preferences develop during early childhood and contribute to dietary patterns that can track into adulthood, it is critical to support healthy food environments in places where children spend significant amounts of time in, such as childcare. It is important to understand what factors influence the diet quality of children cared for in family childcare homes (FCCH). Methods: This study used baseline data from a cluster-randomized trial in FCCH, Healthy Start/Comienzos Sanos. Surveys capturing provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Dietary behaviors are developed rapidly from infancy to adolescence, and they are influenced not only by individual factors and household characteristics [ 1 ], but also by parent–child interactions and social interactions [ 2 ]. In the adolescence period, dietary behaviors may be crucial, as they contribute to further behaviors in adulthood and to the resultant health risks [ 3 ] associated with body mass [ 4 ] and dieting [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary behaviors are developed rapidly from infancy to adolescence, and they are influenced not only by individual factors and household characteristics [ 1 ], but also by parent–child interactions and social interactions [ 2 ]. In the adolescence period, dietary behaviors may be crucial, as they contribute to further behaviors in adulthood and to the resultant health risks [ 3 ] associated with body mass [ 4 ] and dieting [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies conducted during the COVID-19 pandemic have revealed important determinants that might influence the dietary behaviors of adults [ 19 , 20 , 21 ], but thus far, no such studies in a population of adolescents have been published. Despite the fact that the determinants of dietary behaviors are generally numerous and complex [ 1 , 2 ], such dietary behaviors in adults during the COVID-19 pandemic can be explained by two major determinants: lockdown and stockpiling food at home [ 20 ]. Both determinants were also experienced by children and adolescents in this period, and may have also influenced their dietary behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A previous analysis of data from the Healthy Start study, found that children under the care of Latino FCCPs had higher diet quality (Healthy Eating Index: 64.4) compared to non-Latino FCCPs (Healthy Eating Index: 56.6). While this study found that children under the care of Latino FCCPs had higher component diet quality scores for greens/beans, total protein, and seafood and plant protein, this analysis did not take into account the specific types of foods offered and the ethnic differences in the foods provided [24]. While the CACFP is a very important predictor of the nutritional quality of foods served in childcare [30][31][32][33], exploring other factors among FCCHs that care for underserved children is needed.…”
Section: Introductionmentioning
confidence: 87%
“…In addition to participating in the CACFP, FCCH providers (FCCPs) are ethnically diverse [22], and their ethnicity has been related to different dietary practices in childcare settings [23,24]. Research also suggests that cultural and social differences play a role in the foods offered to children [22,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Most research exploring the nutrition environment in ECEC services has been conducted with centre-based services, with little on FDC (10,11) . Studies involving direct observation in Family Child Care Homes (equivalent to FDC) in the USA have found children's diet quality has been associated with the food provided (12,13) , nutrition education (12) , nutrition policy (12) , educator income (14) , ethnicity (14) and main language spoken at home (14) . Additionally, children were not being provided with, or consuming, adequate amounts of vegetables, total protein foods, seafood and plant-based proteins and wholegrains (13) .…”
mentioning
confidence: 99%